Artificial Intelligence Applications in Nursing - Ahmed, Noha (European Journal of Applied Sciences, 2023)
Artificial intelligence (AI) is considered as a technique to train computers to mimic human cognitive activities including reasoning, learning, decision making and real time communication. It is the new future and often regarded as super intelligence. While the world is rapidly transforming towards virtual spaces and global village theme and transforming our living mode, work cultures and interests, AI can be regarded as the driving force behind these major transformations. As per recent study conducted, global AI healthcare innovations would spike up with an estimated spending of about $ 36.5 billion by 2025. (1) This research article will provide a brief overview of Artificial Intelligence and how it transforms the medical world. It focuses on major transformations in nursing field with the help of AI and the way its automating manual tiresome and recurring tasks performed by nurses to auto scheduled jobs. While AI based techniques are applied in nursing for enhanced patient care, decision making, and service delivery, it has brought advancements in health care outcomes.